1992
DOI: 10.1248/cpb.40.202
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Gastrointestinal Prokinetic Activity and Structure-Activity Relationships of Novel N-((2-(Dialkylamino)ethoxy)benzyl)benzamide Derivatives.

Abstract: Novel N-[[dialkylamino)ethoxy]benzyl]benzamide derivatives (II-1-51), derived from the structural modification of metoclopramide (I), were synthesized and examined for their pharmacological activities. Among them, N-[4-[2-(dimethylamino)ethoxy]benzyl]-3,4-dimethoxybenzamide (II-34) which exhibited well balanced gastrointestinal prokinetic and antiemetic activities was selected as a new type of gastrointestinal prokinetic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…These data suggested that HSR-803 stimulated gastric motility through dopamine-D2-receptor blocking and AChE inhibition. Sakaguchi et al (4) have already reported that the anti-AChE activity of some new ly synthesized benzamide derivatives, including HSR-803, was closely related to the motor-stimulating activity in the ileum. Recently, we (5) have been able to study the steady peristalsis of the ileum for a few hours in vitro by a pro cedure based on the method of Bulbring and Lin, with modifications (6).…”
Section: Hsr-803 (N-[4-[2-(dimethylamino)ethoxy]benzyl]-34 Dimethoxymentioning
confidence: 97%
“…These data suggested that HSR-803 stimulated gastric motility through dopamine-D2-receptor blocking and AChE inhibition. Sakaguchi et al (4) have already reported that the anti-AChE activity of some new ly synthesized benzamide derivatives, including HSR-803, was closely related to the motor-stimulating activity in the ileum. Recently, we (5) have been able to study the steady peristalsis of the ileum for a few hours in vitro by a pro cedure based on the method of Bulbring and Lin, with modifications (6).…”
Section: Hsr-803 (N-[4-[2-(dimethylamino)ethoxy]benzyl]-34 Dimethoxymentioning
confidence: 97%
“…A mixture of 12 (2.79 g, 9.80 mmol) and ethyl acrylate (1.35 ml, 12.5 mmol) in EtOH (28 ml) was refluxed for 4 h. The reaction mixture was concentrated and the residue was washed with iso-Pr 2 O to afford pale yellow crystals (3.34 g, 87%), which were recrystallized from a mixture of acetone and Et 2 85 (1H, m), 3.84 (3H, s), 4.06 (2H, q, Jϭ7.0 Hz), 5.70-5.85 (2H, br s), 6.49 (1H, s), 7.60-7.75 (1H, m), 7.66 (1H, s).…”
Section: Ethyl 4-[(4-amino-5-chloro-2-methoxybenzoyl)amino]-1-piperidmentioning
confidence: 99%
“…We previously reported that the introduction of a methylenephenoxy group between the benzamide moiety and the terminal aminoalkyl groups of 1a led to the discovery of itopride (2), with an appropriate dopamine D 2 receptor antagonist activity and a distinctive acetylcholine esterase inhibitory activity. 2) On the other hand, we suggested that amphoteric-ionization would be a useful approach to discovering a new drug, and actually succeeded in finding selective histamine H 1 antagonists by applying this method to classical antihistaminics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Itopride enhances ACh-induced contraction of guinea pig ileum, but not carbachol-induced contraction (2). Sakaguchi et al reported that AChE inhibition by some newly synthesized benzamide derivatives, including itopride, is closely related to the contractile response of the ileum (3). AChE inhibitors stimulate gastrointestinal motor activity, and neostigmine has been used to treat in testinal paresis.…”
mentioning
confidence: 99%